Efektivitas metode promosi kesehatan melalui media video edukasi aplikasi tiktok terhadap pengetahuan dan sikap tentang tindakan pencegahan stunting pada kader posyandu - Hafiz Nayotama Hafiz Nayotama; Tubagus Erwin; Nurul Aziza (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: Stunting is a condition of growth failure in children under five caused by chronic malnutrition and recurrent infections, characterized by height or length below the standard for age. According to the 2023 Indonesia Health Survey, the prevalence of stunting is 21.5%, with the highest incidence among children aged 2–3 years. In the working area of Sinar Rezeki Community Health Center, South Lampung Regency, stunting cases remain high, reaching 723 children. Effective stunting prevention efforts require improving the knowledge and attitudes of Posyandu cadres through health promotion, one of which is by utilizing educational video media on the TikTok application. Purpose: To determine the effectiveness of health promotion through educational video media on the TikTok application towards knowledge and attitude regarding stunting prevention among Posyandu cadres. Method: This study is quantitative with a one-group pretest-posttest design. The population consisted of 80 Posyandu cadres, with a total sample of 41 respondents selected using proportional sampling. Data were collected using questionnaires and analyzed using univariate and bivariate methods, with the Wilcoxon test applied for bivariate analysis. Results: The average knowledge score before the intervention was 47.80 (SD 8.22), which increased to 71.22 (SD 7.14) after the intervention. The average attitude score before the intervention was 72.68 (SD 8.6), which increased to 91.04 (SD 3.62) after the intervention. The Wilcoxon test result showed a p-value = 0.001, indicating a significant effect of TikTok educational videos on increasing knowledge and attitudes of Posyandu cadres regarding stunting prevention. Conclusion: Educational video media on the TikTok application is effective in improving the knowledge and attitudes of Posyandu cadres towards stunting prevention in the working area of Sinar Rezeki Community Health Center. Suggestion: The use of TikTok-based educational video media should be further enhanced and implemented sustainably in health promotion programs, as it has been proven effective in improving knowledge and attitudes of Posyandu cadres in stunting prevention efforts